BOOK REVIEW-IMMUNITY TO CHANGE - Bertone, Santina (The journal of contemporary issues in business and government, 2013)
In an era of ‘Supercapitalism’1 competition is unrelenting and ubiquitous. Innovation and change become the keys to survival for organisations. Yet the human factors in organisations are often last to change in response to these pressures. In Peter Hayward’s review of Immunity to Change we learn there are tools to uncover the deep seated psychological barriers to change within organisations and how to expose those barriers so that they can be tackled. Peter Hayward’s review explains how people in organisations don’t mindlessly cling to old attitudes and ways of doing things. They do so because of the power of assumptions – myths, misconceptions, fallacies – that validate their way of operating. His review notes the practical ways proposed in Kegan and Lahey’s book to address these barriers and connect successfully with the people issues in organisations. As such, the book is of potential benefit to all innovators, whether they be in business, government or the not-for-profit sector.